Synthesis of new glassy Mg-Ca-Zn alloys with exceptionally low Young's Modulus: Exploring near eutectic compositions. (December 2019) - Bera, Supriya; Paul, Sudeep; Ramasamy, Parthiban; Mandal, Durbadal; Das, Mitun; Lassnig, Alice; Renk, Oliver; Calin, Mariana; Eckert, Jürgen
Abstract: We report two new magnesium-rich glassy Mg-Ca-Zn alloys of one eutectic (Mg72 Ca12 Zn16 ) and another near eutectic (Mg63 Ca15 Zn22 ) composition. The glass-forming ability of the alloys is slightly lower than that of the Mg60 Ca5 Zn35 alloy which has been well explored earlier. The Young's Modulus of the new glassy alloys is exceptionally low (~35 GPa) and much lower than that of the Mg60 Ca5 Zn35 glassy alloy (~50 GPa) indicating possible potential biomedical applications. Graphical abstract: Unlabelled Image